Analysis of the Electric Dipole Moment in the R-parity Violating Supersymmetric Standard Model - Yamanaka, Nodoka (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
In this thesis the author discusses the phenomenology of supersymmetric models by means of experimental data set analysis of the electric dipole moment. There is an evaluation of the elementary processes contributing to the electric dipole moments within R-parity-violating supersymmetry, which call for higher-order perturbative computations. A new method based on linear programming is developed and for the first time the non-trivial parameter space of R-parity violation respecting the constraints from existing experimental data of the electric dipole moment is revealed. As well, the impressive efficiency of the new method in scanning the parameter space of the R-parity-violating sector is effectively demonstrated. This new method makes it possible to extract from the experimental data a more reliable constraint on the R-parity violation.